The Garlic Allelochemical Diallyl Disulfide Affects Tomato Root Growth by Influencing Cell Division, Phytohormone Balance and Expansin Gene Expression - Cheng, Fang; Cheng, Zhihui; Meng, Huanwen; Tang, Xiangwei (Frontiers in Plant Science, 2016)
Diallyl disulfide (DADS) is a volatile organosulfur compound derived from garlic (Allium sativum L.), and it is known as an allelochemical responsible for the strong allelopathic potential of garlic. The anticancer properties of DADS have been studied in experimental animals and various types of cancer cells, but to date, little is known about its mode of action as an allelochemical at the cytological level. The current research presents further studies on the effects of DADS on tomato (Solanum lycopersicum L.) seed germination, root growth, mitotic index and cell size in root meristem, as well as the phytohormone levels and expression profile of auxin biosynthesis genes (FZYs), auxin transport genes (SlPINs) and expansin genes (EXPs) in tomato root. The results showed a biphasic, dose-dependent effect on tomato seed germination and root growth under different DADS concentrations. Lower concentrations (0.01-0.62 mM) of DADS significantly promoted root growth, whereas higher levels (6.20-20.67 mM) showed inhibitory effects. Cytological observations showed that the cell length of root meristem was increased and that the mitotic activity of meristematic cells in seedling root tips was enhanced at lower concentrations of DADS. In contrast, DADS at higher concentrations inhibited root growth by affecting both the length and division activity of meristematic cells. However, the cell width of the root meristem was not affected. Additionally, DADS increased the IAA and ZR contents of seedling roots in a dose-dependent manner. The influence on IAA content may be mediated by the up-regulation of FZYs and PINs. Further investigation into the underlying mechanism revealed that the expression levels of tomato EXPs were significantly affected by DADS. The expression levels of EXPB2 and beta-expansin precursor were increased after 3 d, and those of EXP1, EXPB3 and EXLB1 were increased after 5 d of DADS treatment (0.41 mM). This result suggests that tomato root growth may be regulated by multiple expansin genes at different developmental stages. Therefore, we conclude that the effects of DADS on the root growth of tomato seedlings are likely caused by changes associated with cell division, phytohormones and the expression levels of expansin genes.